The Influence of Halal Marketing Strategy, Product Quality, and Price On Skincare Purchase Decisions in Masamba - Miranda; Suhardi M. Anwar; Rahmawati (SIMAK, 2026)
This study aims to examine the influence of halal marketing strategies, product quality, and price on consumer decisions to purchase halal skincare in Masamba District. This research is motivated by increasing public awareness of the importance of using halal products, especially among young women as the main users of skincare. The study used a quantitative approach with primary data collected through questionnaires from 115 respondents who use halal skincare. Data analysis was conducted using the SmartPLS 3.0 application to test validity, reliability, and relationships between variables. The results showed that halal marketing strategies, product quality, and price had a positive and significant effect on purchasing decisions. The coefficient of determination (R²) value of 0.718 indicates that 71.8% of the variation in purchasing decisions can be explained by these three variables, while the remaining 28.2% is influenced by other variables outside the research construct. These findings indicate that the implementation of Islamic value-based marketing strategies, superior product quality, and competitive prices can increase consumer trust and encourage purchasing decisions for halal skincare. Thus, a combination of halal marketing strategies, improving product quality, and setting appropriate prices are key factors in strengthening the competitiveness of halal skincare products.